2023
DOI: 10.1002/adfm.202305995
|View full text |Cite
|
Sign up to set email alerts
|

Nacre‐Inspired Metal‐Organic Framework Coatings Reinforced by Multiscale Hierarchical Cross‐linking for Integrated Antifouling and Anti‐Microbial Corrosion

Abstract: A long‐standing quest in marine materials science has been the development of tough and effective antifouling coatings for diverse surface protection. However, most commercial coatings are severely limited by poor mechanical behavior and unsustainable passive biocidal effect, leading to irreversible marine biofouling and even microbiologically influenced corrosion (MIC). Herein, inspired by the amorphous/crystalline feature within nacreous platelets, a mechanically robust antifouling coating composed of biopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…‘Smart coatings’ encapsulate antimicrobial substances or compounds that repair metal damage and respond to environmental stimuli (Udoh et al, 2022 ; Yu et al, 2023 ). For example, a metal‐organic framework (MOF) zeolitic imidazolate framework‐8 (ZIF‐8) preloaded with metronidazole or hollow mesoporous silica nanoparticles specifically responded to the activity of sulphate reducers, diminishing their corrosive activity (Cai et al, 2021 ; Tang et al, 2023 ).…”
Section: What Are the Current Methods For Preventing Corrosive Biofil...mentioning
confidence: 99%
“…‘Smart coatings’ encapsulate antimicrobial substances or compounds that repair metal damage and respond to environmental stimuli (Udoh et al, 2022 ; Yu et al, 2023 ). For example, a metal‐organic framework (MOF) zeolitic imidazolate framework‐8 (ZIF‐8) preloaded with metronidazole or hollow mesoporous silica nanoparticles specifically responded to the activity of sulphate reducers, diminishing their corrosive activity (Cai et al, 2021 ; Tang et al, 2023 ).…”
Section: What Are the Current Methods For Preventing Corrosive Biofil...mentioning
confidence: 99%
“…It is a promising result, indicating that the functionalization of Ti 60 Zr 20 Si 8 Ge 7 B 3 Sn 2 MG ribbons with tannic acid reduces the thickness of bacterial biofilm-like structures to single and random colonies; development of anticorrosion and antibacterial materials by modifying their surfaces’ properties or coating them was reported in the previous literature. 63 65 Despite bacterial aggregations, single colonies are very sensitive to antibiotics, and they can be easily removed from the transmucosal parts of dental implants using antiseptic mouthwash containing, for example, chlorhexidine gluconate, cetylpyridinium, and essential oils. 66 So, it can be speculated that this antiaggregation effect can be due to the presence of the tannic acid, as previously shown by Schestakow et al; 67 in fact, they reported a reduction of bacterial viability and surface-adhered bacterial cells on dentin specimens by rinsing them with a solution containing tannic acid due to the interaction of bioactive groups in tannic acid with bacterial cell membranes and proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed coatings have emerged as a promising method with which to enhance the protection against microbial corrosion by combining the benefits of organic and inorganic coatings. These coatings are composed of two or more materials and have shown improved corrosion resistance and mechanical properties [ 108 ]. Of particular interest is the polymer-ceramic blend, which exhibits unique properties such as self-healing and thermal stability, and has been the subject of significant research [ 109 ].…”
Section: Marine Mic Inhibitionmentioning
confidence: 99%